Gas well deliquification solutions to gas well liquid loading problems - Lea, James Fletcher
No other book on the market offers such a turnkey solution to the problem of liquid interference in gas wells. Gas Well Deliquification contains not only descriptions of the various methods of de-watering gas wells, but also compares the various methods with a view toward explaining the suitability of each under particular circumstances. The material is presented as practical information that can be immediately applied, rather than a theoretical treatment. And, includes useful historical methods, but focuses on the latest techniques for de-watering gas wells. * Only book on market to offer a turnkey solution to the problem of liquid interference in gas wells * Contains descriptions of the various methods of de-watering gas wells, as well as comparing the various methods with a view to explaining the suitability of each under particular circumstances * Introduces material as practical information that can be immediately applied, rather than a theoretical treatment.